Investigating The Impact Of Teacher Talk On Learners’ Involvement In Algerian Secondary School Classrooms - Radia Dine (The Journal of Studies in Language, Culture and Society, 2024)
The present study is an exploratory research aimed towards investigating the impact of teachers’ talk on learners’ involvement in the EFL classroom. It is an attempt to shed some light on the centrality of teacher talk in providing or hindering learning opportunities for EFL learners, especially at the secondary level. To reach these aims, a mixed method approach was opted for; a classroom observation of six secondary school teachers. In addition, a questionnaire administered to 103 learners to have an overview about their viewpoints regarding their teachers’ use of pedagogic discourse that is influential to their involvement in the classroom. The results have revealed invaluable remarks that highlight the interplay between discourse and learners’ involvement in the EFL classroom. In addition, recommendations have been put forward as an attempt to contribute to teachers’ professional development with regard to interaction and discourse in the EFL classroom.